2017
DOI: 10.1364/ol.42.000995
|View full text |Cite
|
Sign up to set email alerts
|

Extended depth-of-field microscopy with a high-speed deformable mirror

Abstract: We present a wide-field fluorescence microscopy add-on that provides a fast, light-efficient extended depth-of-field (EDOF) using a deformable mirror with an update rate of 20 kHz. Out-of-focus contributions in the raw EDOF images are suppressed with a deconvolution algorithm derived directly from the microscope 3D optical transfer function. Demonstrations of the benefits of EDOF microscopy are shown with GCaMP-labeled mouse brain tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(76 citation statements)
references
References 25 publications
3
69
0
1
Order By: Relevance
“…As expected, when the acoustic lens was turned on ( Figure 3A), the excitation beam was scanned multiple times over the z-axis at each pixel, and consequently, the integration of the pixel information resulted in an extension in the axial PSF from 1.5 μm to about 30 μm (FWHM values). Note that the achieved axial scanning range was in agreement with the theoretical value of 35 μm [30,45]. Importantly, the lateral PSF throughout the whole scanning range (average FWHM = 0.60 μm) was comparable to the in-focus PSF with lens off (FWHM ' 0.55 μm) ( Figure 3B,C).…”
Section: Fast Volumetric Imagingsupporting
confidence: 85%
“…As expected, when the acoustic lens was turned on ( Figure 3A), the excitation beam was scanned multiple times over the z-axis at each pixel, and consequently, the integration of the pixel information resulted in an extension in the axial PSF from 1.5 μm to about 30 μm (FWHM values). Note that the achieved axial scanning range was in agreement with the theoretical value of 35 μm [30,45]. Importantly, the lateral PSF throughout the whole scanning range (average FWHM = 0.60 μm) was comparable to the in-focus PSF with lens off (FWHM ' 0.55 μm) ( Figure 3B,C).…”
Section: Fast Volumetric Imagingsupporting
confidence: 85%
“…While lateral 2D-scans can achieve video rate by employing resonant scanners or acousto-optic deflectors, a sufficiently fast modulation of the axial focus position is still challenging. Partly in response to this specific demand, in recent years several technologies have been developed to tune the optical power of lenses (Berge, 2005;Ren et al, 2006;Bernet et al, 2013) or Micro-Electro-Mechanical System mirrors (Qi et al, 2004;Shain et al, 2017). Some of these systems, like the tunable polymer-filled lenses (Ren et al, 2006;Jabbour et al, 2014;Nakai et al, 2015) or lenses based on electrowetting (Berge, 2005) are now available.…”
Section: Introductionmentioning
confidence: 99%
“…The core of our technique involves sweeping the focal plane of a microscope at an axial position z s over a scan range D. There are many ways of implementing a focal sweep system [15]; while any such system would be acceptable, our method is to insert a deformable mirror (DM) into the back focal plane, or pupil plane, of an otherwise standard epi-fluorescence microscope (described in [22]). The curvature of the DM can be swept from positive to negative, causing the focal plane of the microscope to sweep over a scan range from z s = − D 2 to z s = D 2 , during a single camera exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The curvature of the DM can be swept from positive to negative, causing the focal plane of the microscope to sweep over a scan range from z s = − D 2 to z s = D 2 , during a single camera exposure. The key benefits of using a DM are light efficiency, achromaticity, speed (we use a DM that provides a 20kHz update rate), and scan range (we have shown that even with a modest DM stroke of 2.5 − 3µm, we can extend the standard depth of field of the microscope by ≈ 70× [22]). In existing focal-sweeping systems, the EDOF image is a single-shot projection of Fig.…”
Section: Introductionmentioning
confidence: 99%